Evaluation of the quality of an image encrytion scheme - Osemwegie Omoruyi; Chinonso Okereke; Kennedy Okokpujie; Etinosa Noma-Osaghae; Obinna Okoyeigbo; Samuel John (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Encryption systems have been developed for image viewing applications using the Hill Cipher algorithm. This study aims to evaluate the image encryption quality of the Hill Cipher algorithm. Several traditional metrics are used to evaluate the quality of the encryption scheme. Three of such metrics have been selected for this study. These include, the Colour Histogram, the Maximum Deviation (comparing the original image) and the Entropy Analysis of the encrypted image. Encryption quality results from all three schemes using a variety of images show that a plain Hill Cipher approach gives a good result for all kinds of images but is more suited for colour dense images.